Oesophageal carcinoma with solitary patellar metastasis: a rare case report. Issue 4 (April 2021) - Zhao, Yi; Zhang, Qianqian; Feng, Helin; Zhu, Xiyan
The incidence of tumours found in the patella, including primary and metastatic tumours, is low. Solitary metastasis of oesophageal carcinoma (OC) in the patella is even rarer. A 50-year-old man presented to our clinic because of pain and limited range of motion in the right knee for 4 hours and after a fall. On the basis of the patient's medical history, he was diagnosed with OC 2 months previously and underwent two cycles of paclitaxel liposome combined with tiggio chemotherapy (oral tiggio, 40 mg, two times/day, with a treatment cycle of 3 weeks). A 99mTc-methylene diphosphonate bone scintigraphy scan showed increased radioactivity in the right patella. A right knee biopsy showed the presence of patellar metastasis from OC. Unfortunately, the patient denied additional treatment and was discharged for personal reasons. At the 1-month follow-up, which was conducted by a telephone survey, we learned that the patient had died of acute pulmonary embolism. X-rays and computed tomography are useful for diagnosing patellar metastases, but 99mTc-methylene diphosphonate bone scintigraphy can help physicians diagnose patellar metastasis of OC more rapidly. Biopsy with pathology is the gold standard for diagnosing patellar metastases. Additionally, timely surgical treatment prolongs the survival time of these patients.